Mechanical Properties of Eco-friendly Concrete Made with Sugarcane Bagasse Ash - Tareg Abdalla Abdalla; David O. Koteng; Stanley M. Shitote; M. Matallah (Civil Engineering Journal, 2022)
Modern concretes lay emphasis on high strength in order to reduce structural member sizes to reduce materials used; high early strength to promote fast construction; high durability to reduce maintenance costs; and the incorporation of industrial and agricultural wastes to reduce environmental degradation. The incorporation of industrial and agricultural wastes into concrete as cement replacement materials reduces the amount of cement used in the production of concrete and the CO2emissions arising from cement production. Sugarcane bagasse is a waste product from the extraction of juice from sugar cane. It is estimated that 1.7 million tons of bagasse are produced worldwide every year. Much of the bagasse is used as boiler fuel and to produce electricity, and the ash is dumped in earth fills, resulting in critical environmental pollution that requires immediate attention. Available literature shows that when burned under controlled conditions, a pozzolanic ash of high silica content can be obtained, which can be used in concrete production with several advantages. This study investigates the mechanical properties of concrete designed for high strength and incorporating processed sugarcane bagasse ash in amounts of 10–40% by weight of cement in a binary combination with silica fume. Concrete workability in the fresh state and compressive, flexural, and tensile strengths in the hardened state are investigated. Water absorption of hardened concrete is also investigated as an indicator of potential durability. The results show that the mix containing 10% SCBA has the highest mechanical strength, and increasing the SCBA percentage reduces water absorption. However, the workability of concrete in the fresh state reduces substantially with an increase in ash content. Doi: 10.28991/CEJ-2022-08-06-010 Full Text: PDF